T Cell–Macrophage Interactions and Granuloma Formation in Vasculitis - Hilhorst, Marc; Shirai, Tsuyoshi; Berry, Gerald; Goronzy, Jörg J.; Weyand, Cornelia M. (Frontiers in Immunology, 2014)
Granuloma formation, bringing into close proximity highly activated macrophages and T cells, is a typical event in inflammatory blood vessel diseases, and is noted in the name of several of the vasculitides. It is not known whether specific properties of the microenvironment in the blood vessel wall or the immediate surroundings of blood vessels contribute to granuloma formation and, in some cases, generation of multinucleated giant cells. Granulomas provide a specialized niche to optimize macrophage-T cell interactions, strongly activating both cell types. This is mirrored by the intensity of the systemic inflammation encountered in patients with vasculitis, often presenting with malaise, weight loss, fever and strongly upregulated acute phase responses. As a sophisticated and highly organized structure, granulomas can serve as an ideal site to induce differentiation and maturation of T cells. The granulomas possibly seed aberrant Th1 and Th17 cells into the circulation, which are known to be the main pathogenic cells in vasculitis. Through the induction of memory T cells, aberrant innate immune responses can imprint the host immune system for decades to come and promote chronicity of the disease process. Improved understanding of T cell-macrophage interactions will redefine pathogenic models in the vasculitides and provide new avenues for immunomodulatory therapy.